Rethinking The Replaceability Of Accounting Jobs: A Critical Review - Amelia Rizky Alamanda (Bajang Institute, 2026)
This study critically reviews the replaceability of accounting jobs in the context of increasing automation and digitalization. Rather than treating technological capability at the task level as direct evidence of occupational replacement, the review examines how task-level changes may be redistributed and translated into changes in accounting jobs and professional roles. A critical literature review was conducted using a bounded initial dataset of 31 Scopus-derived records. Three anchor studies were used to develop initial propositions, which were then examined through proposition-based cross-examination with additional theoretical and empirical evidence. The review produces three main findings. First, task automation does not necessarily imply occupational replacement because accounting activities may be automated, augmented, retained, or redistributed. Second, occupational survival does not automatically lead to professional upgrading; technological change may be associated with role expansion, specialization, hybridization, changing professional boundaries, or deskilling. Third, technological competency requirements differ across career stages, suggesting a distinction between current entry-level requirements and longer-term professional development. Overall, the review identifies task redistribution as an important link between technological change and changes in accounting jobs. The replaceability of accounting jobs is therefore better understood through how work is redistributed and recombined, rather than through technological capability alone.